Гэр бүл - XXI зуун - Намжил, Т. (Historia Mongolarum, 2003)
The issue concerning the modern families has been becoming the central point of not only a single country but also diverse regions, continents and, moreover, the world. In the coming 5 to 15 years , family relations , especially of young families, will be addressed specificаlly. From the ancient times people in the Central Asia and Mongolia have been engaged in a single way of life leading them to retain the dominant nuclear family form. However, the changes appeared in the family compositions in European countries and the United States are likely to affect the Mongolian way.